Medical Science and Physics - Lamsal, Min Raj (Himalayan Physics, 2015)
The study of physics seems to be theoretical or abstract. The connections between physics and real life can seem remote. But in reality physics is not a purely abstract subject. Like other branches of science, physics has a pure theoretical side and an applied side. The principles of physics are applied in a vast range of contexts from the building of bridges to the design of integrated circuits. Much of the technological revolution has its foundations in the applied physics. One of the major applications of physics which covers vast area of scientific knowledge is medicine. The knowledge of physics is essential for ultrasound, hologram, X-rays, laser therapy, radiotherapy, endoscopy, MRI, CT scanning, ECG, EEG, PET and so on in the field of medical science. The theoretical principles have to be learned and understood first if the applications are to be understood The Himalayan Physics Vol. 5, No. 5, Nov. 2014 Page: 91-97